2016
DOI: 10.1038/srep39571
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry imaging of biomarker lipids for phagocytosis and signalling during focal cerebral ischaemia

Abstract: Focal cerebral ischaemia has an initial phase of inflammation and tissue injury followed by a later phase of resolution and repair. Mass spectrometry imaging (desorption electrospray ionization and matrix assisted laser desorption ionization) was applied on brain sections from mice 2 h, 24 h, 5d, 7d, and 20d after permanent focal cerebral ischaemia. Within 24 h, N-acyl-phosphatidylethanolamines, lysophosphatidylcholine, and ceramide accumulated, while sphingomyelin disappeared. At the later resolution stages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 63 publications
5
59
1
1
Order By: Relevance
“…They identified 11 upregulated phospholipids, including lysophosphatidylcholine (LPC), phosphatidylcholine (PC), and sodiated forms of sphingomyelin (SM) and PCs, as well as 7 downregulated phospholipids in the areas with ischemic damage. Nielsen et al [24] used desorption electrospray ionization and MALDI to study the expression of different phospholipid molecules in the brain at different time points after pMCAO. In this study, 1,5-DAN hydrochloride solution was used as a matrix, and mass spectrometry imaging was used to investigate changes in four phospholipid molecules (PE, PA, PI, and PS) in the ischemic brain.…”
Section: Discussionmentioning
confidence: 99%
“…They identified 11 upregulated phospholipids, including lysophosphatidylcholine (LPC), phosphatidylcholine (PC), and sodiated forms of sphingomyelin (SM) and PCs, as well as 7 downregulated phospholipids in the areas with ischemic damage. Nielsen et al [24] used desorption electrospray ionization and MALDI to study the expression of different phospholipid molecules in the brain at different time points after pMCAO. In this study, 1,5-DAN hydrochloride solution was used as a matrix, and mass spectrometry imaging was used to investigate changes in four phospholipid molecules (PE, PA, PI, and PS) in the ischemic brain.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, an MS imaging study revealed that sphingolipid changes, such as ceramide increase and SM decrease, in the early phase in cerebral inflammation and dihydroxy derivates of docosahexaenoic and docosapentaenoic acid, some of which may be proresolving mediators ( e.g. , resolvins) were found in the injured area of the resolution phase (39). We investigated whether SMS2 deficiency showed the effect on resolvins in colorectal inflammation and noticed that gene expression of resolvin E1 receptor ( Cmklr1 ), which is expressed on intestinal epithelial cells and interacts with resolvin E1, was 1.8‐fold higher by whole‐genome mRNA microarray analysis in SMS2 −/− cells compared with WT cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The D-series resolvin substrate, DHA is enriched in the brain post cerebral ischemia during the inflammatory response and accumulates in the ischemic area post-surgical survival [22]. The biosynthesis of D-series resolvins involves metabolic conversion of DHA to monohydroperoxy precursors which then undergo enzymatic conversion into specific resolvins [23].…”
Section: Introductionmentioning
confidence: 99%
“…21 The D-series resolvin substrate, DHA, is enriched in the brain postcerebral ischemia during the inflammatory response and accumulates in the ischemic area postsurgical survival. 22 The biosynthesis of D-series resolvins involves metabolic conversion of DHA to monohy-droperoxy precursors, which then undergo enzymatic conversion into specific resolvins. 23 Resolvin D4 (RvD4: 4S,5R,17S-trihydroxydocosa-6E,8E,10Z,13Z,15E,19Z hexaenoic acid) was first identified in selflimited mouse exudates and human leukocytes, 23 and its complete stereochemistry was recently established.…”
Section: Introductionmentioning
confidence: 99%